Pengaruh Gaya Kepemimpinan, Kepuasan Kerja Dan Komitmen Organisasi Terhadap Kinerja Guru (Pada SMK Muhammadiyah Kabupaten Gunungkidul) - Yanuarti, Endah; Suparman W, Aris (208-7721)
The aims of the is to analyze the influence of leadership style, job satisfaction and organizational commitment on teacher performance on SMK Muhammadiyah Gunungkidul. The object of the research are teachers of SMK Muhammadiyah 1 Wonosari, SMK Muhammadiyah 1 Patuk and SMK Muhammadiyah 1 Tepus Gunungkidul. The sample of this research are 121 teachers. The data collecting methods used a questionnaire methods. The research shown that leadership style, job satisfaction and organizational commitment can contribution positive influence on teacher performance. The dominant variables which influences the work performance is commitment organization.Keywords: Teacher performance, Leadership style, Job satisfaction, Organizational commitment.